Fatty acid compositions of Zea mays L. varieties in Turkey - Yrürdurmaz, Cengiz; Yildiz, Hasan (Progress in Nutrition, 2022)
Physical and chemical characteristics of oils are determined by the rate and composition of the fatty acids they have. Knowing the fatty acid composition of oils will enable the production of oils according to intended usage areas. The present study was conducted to determine the fatty acid composition of 20 different corn varieties grown in Turkey. The oil contents of the samples were determined with the Soxhelet Oil Extraction Device, and the fatty acid composition was determined with the GC-S/FID Device. The dominant fatty acids of the cultivars and lines that were examined in the scope of the present study were found to be linoleic acid (50.05-53.14%), oleic acid (31.09-33.21%), palmitic acid (11.07-13.16%), stearic acid (2.10-2.55%), linolenic acid (0.55-1.18%), and arachidic acid (0.36% - 0.53%). It was found that the differences between cultivars were very significant for all the characteristics studied here except for lauric acid. The findings of the study show that there is a wide variation in fatty acid composition in the existing cultivars and lines.